2008
DOI: 10.1002/eat.20535
|View full text |Cite
|
Sign up to set email alerts
|

Heat reversal of activity‐based anorexia: Implications for the treatment of anorexia nervosa

Abstract: From a translational perspective, these findings offer a fresh perspective to the disorder, and underscore the need for further studies to assess the effects of heat treatment in patients as an innovative adjunctive treatment for anorexia nervosa.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 45 publications
3
23
0
1
Order By: Relevance
“…This thermogenic response might also contribute to the observed decrease in body weight. However, it is important to note that activity-based anorexia was associated with a hypothermic response before (Hillebrand et al, 2005a) and an increase in ambient temperature was reported to reduce physical activity (Gutierrez et al, 2008). Future studies should further investigate these—likely very dynamic—changes of body temperature in activity-based anorexia rats.…”
Section: Discussionmentioning
confidence: 99%
“…This thermogenic response might also contribute to the observed decrease in body weight. However, it is important to note that activity-based anorexia was associated with a hypothermic response before (Hillebrand et al, 2005a) and an increase in ambient temperature was reported to reduce physical activity (Gutierrez et al, 2008). Future studies should further investigate these—likely very dynamic—changes of body temperature in activity-based anorexia rats.…”
Section: Discussionmentioning
confidence: 99%
“…These findings may be a specific instance of a more general rule, which is also manifested in the largely overlooked worldwide association of the incidence of AN and geographical latitude, as can be seen from a bibliometric study showing that 72% of AN references in the Northern Hemisphere were located within a 15° latitude range (40°N–55°N) . Furthermore, research on an analogous animal model of anorexia nervosa known as activity‐based anorexia (ABA) has provided experimental data on the beneficial impact of increasing AT over the thermoregulatory threshold both in the prevention and reversion of weight loss, and in the excessive activity and reduced food intake exhibited by animals exposed to the ABA procedure …”
Section: Introductionmentioning
confidence: 87%
“…9 Furthermore, research on an analogous animal model of anorexia nervosa known as activity-based anorexia (ABA) has provided experimental data on the beneficial impact of increasing AT over the thermoregulatory threshold both in the prevention and reversion of weight loss, and in the excessive activity and reduced food intake exhibited by animals exposed to the ABA procedure. 10,11 ANR patients have been consistently reported in the literature to be lighter both on admission and premorbidly in comparison to ANBP patients, 12 but to our knowledge no study had explored seasonal influences on this difference in bodyweight. Due to these differences in bodyweigt we hypothesize that BMI at hospital admission for ANR patients will be more likely affected by AT than ANBP patients.…”
Section: Introductionmentioning
confidence: 87%
“…22 The reasons for increased PAL during acute AN are not entirely clear. It is often assumed that increased PAL is consciously motivated to increase energy expenditure with a resolute goal of facilitating weight loss or maintenance of low weight, but alternative explanations have also been posited including thermoregulation, 23,24 anxiolysis, 25,26 and mood regulation. 21,22 If recovery is characterized by improved thermoregulation, and reduced anxiety and negative affect these motivators could cease to be operative and reasons for physical activity after recovery could differ from reasons for physical activity during the acute phase of the illness.…”
Section: Physical Activitymentioning
confidence: 99%